Interactive Learning Media Assisted by Adobe Flash to Improve Students’ Motivation and Story-reading Skills at the Third Grade of Elementary School - Anggraini, Dinda Tri; Mustadi, Ali (International Journal of Elementary Education, 2024)
The absence of learning media that is appropriate to the objectives of learning reading skills is a problem that exists in elementary schools. Based on these problems, the motivation and story reading skills of students are low. This research aims to create interactive learning media assisted by Adobe Flash that is valid, feasible, and effective in increasing third-grade elementary school students’ motivation and story-reading skills. The research method uses RnD with the ADDIE model development procedure. The research subjects included material and media experts, teachers and third grade elementary school students. Data collection used scales, questionnaires and tests. The data analysis technique is quantitative analysis which is explained by qualitative analysis. The research results were the average validation results by media experts 99.2%, material experts 73.75%, teacher responses 94.05% and student responses 97.31%. The independent t-test and MANOVA research results show significant differences and influence on motivation and story reading skills between students who use and do not use interactive learning media assisted by Adobe Flash. It was concluded that creating interactive learning media assisted by Adobe Flash that was valid, practical and effective could increase the motivation and story reading skills of third grade elementary school students.